(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
At present, India is the most growing powerful nation state of the world. Although it came into being in1947, it was a colony of the British Empire. The British had ruled this land for more than 200 years. To become independent it has to go through a long journey. In this long journey it was guided by its great leaders. These leaders gave Indians the tools to become independent that is Nationalist Movement. Hence, Indian leaders are called the soul of the Indian Nationalist Movement. Mahatma Gandhi has been an apostle of non-violence. However, Gandhi had been and is still misunderstood by many as a leader. Very often he would withdraw a mass movement during India’s freedom struggle against the British. As Gandhi was a firm believer in non-violence and he would never compromise with it. Hence, he would often retort to withdrawing a particular movement. These decisions would often leave many of his followers confused. My paper would highlight on the reasons of Gandhi being misunderstood as a leader not only at the political, social and economic levels but also by his family members.